Peningkatan Pengetahuan Tentang AIDS pada Pekerja Seks Komersial di Panti Sosial Wanita Surakarta - Endang Zulaicha Susilaningsih; Enita Dewi (Universitas Muhammadiyah Surakarta, 2010)
Improving of AIDS desease one of caused by limited of knowledge which the impactof their attitude. Free sex related to the number of HIV viral infecsious. The aim of theactivity is improving of knowledge the commercial sex workers about AIDS desease.AIDS one of the impact commercial sex workes. The methodh of activity are lecture,discussion and consultation. The matherial of AIDS including definition,simptom and sign, treatment and preventive. The rresult of activity is the knowledgeof commercial sex workers better than before health education.